Colorectal Cancer Stratification in the Routine Clinical Pathway: A District General Hospital Experience. Issue 6 (July 2019) - Wedden, Sarah; Miller, Keith; Frayling, Ian M.; Thomas, Teresa; Chefani, Alina; Miller, Karolina; Hamblin, Angela; Taylor, Jenny C.; D'Arrigo, Corrado
Abstract : Colorectal cancer (CRC) has many subtypes with different prognoses and response to treatment. Patients must be characterized to access the most appropriate treatment and improve outcomes. An increasing number of biomarkers are required for characterization but are not in routine use. We investigated whether CRC can be stratified routinely within a small district general hospital to inform clinical decision making at local multidisciplinary team meeting/tumor board level. We evaluated mismatch repair (MMR) and EGFR signaling pathways using predominantly in-house immunohistochemical (IHC) tests (MSH2, MSH6, MLH1, PMS2, BRAF-V600E, Her2, PTEN, cMET) as well as send away PCR/NGS tests (NRAS, KRAS, and BRAF). We demonstrated that many of the tests required for personalized treatment of CRC can be done locally and timely. Send away tests need to be requested shortly after cut-up and this needs to be firmly established in the tissue pathways for the results to be considered at multidisciplinary team meeting/tumor board. We have shown that MMR IHC combined with BRAFV600E IHC is practical and easy to perform in a small district general hospital, has full concordance with DNA-based tests and satisfies the latest NICE requirements for the identification of potential Lynch syndrome patients. We provide a framework for the interpretation and presentation of test results. It is a practical classification that clinical pathologists can use to communicate effectively with the clinical team. It is broadly based on molecular subtyping, firmly focused on treatment decisions and dependent on the panel of molecular tests currently available.